The Effectiveness of Women Empowerment Model in Harmony Women Crisis Center Jombang Regency - Alifiulahtin Utaminingsih; Astrida Fitri Nuryani; Intan Etika Absari (Budapest International Research and Critics University, 2021)
The present study aimed to determine the effectiveness of the women empowerment program implemented by Harmony Women Crisis Center (HWCC) Jombang Regency. Regarding the effectiveness of women empowerment of victims of domestic violence implemented by HWCC, a community named Sekar Arum was established. Consisting of 20 members at the beginning, there were only ten members left. A range of factors accounts for this decrease, despite its importance in developing financially autonomous women in order to prevent domestic violence due to economic factors. The organization optimally put all efforts and resources, such as competent, experienced resources, to assist the victim. Organizations related to the handling of domestic violence are expected to recruit competent employees with linear educational backgrounds. It is necessary to have employees with skills to provide psychological and legal assistance. It is also recommended to improve the collaboration and activity performance by involving village cadres in order to spread the movement in a more sustainable fashion in more villages. It is also necessary for HWCC to allocate special funds for women empowerment activities. Such funds can be proposed to the Department of Women and Children Protection of PPKB PPPA budget. The government should improve its collaboration with HWCC to provide psychological support and recover victims’ social function. Thus, the women victim of violence can be freed from public stigmatization. The regional government of Jombang Regency should take issues on women empowerment as its program focus.